The Transformation of Higher Education in Turkmenistan: Continuity and Change - Victoria Clement; Zumrad Kataeva (My University, 2018)
Over the past century Turkmenistan developed a modern system of higher education that grew from a single university under Moscow’s direction to twenty‑four institutions today. Under Presidents Niyazov and Berdimuhamedow, educational infrastructure expanded dramatically. Despite this growth, the higher education system suffers from a critical lack of faculty, serving fewer than ten percent of high‑school graduates. Curricula still reflect pervasive state ideology. This chapter examines education policy history in post‑Soviet Turkmenistan, focusing on reforms initiated during the regimes of Niyazov (1990–2006) and Berdimuhamedow (2007–present). It analyzes state dominance, demographic challenges, and the limits of institutional expansion in meeting societal needs
Keywords: higher education; Post-Soviet education; Turkmenistan